Nação em processo e identidades em trânsito: a face pós-colonial em o último voo do flamingo, de Mia Couto - Pimenta, Dionisio da Silva (2013)
This work intends to analyse the novel O último voo do flamingo, by Mia Couto, through the postcolonial theory, showing how the narrative constructs a political criticism to the administration of a small village called Tizangara, possible metonymy of Mozambique. In this way, the goals are to demonstrate how some aesthetic resources that the novel uses, such as the satire, the uncommon, the oral tradition and the discursive construction of the difference, work as mechanisms of expurgation of a political corruption and contribute to the fiction to be a way of promoting the catharsis of a postcolonial locus.